2013
DOI: 10.4161/chim.26509
|View full text |Cite
|
Sign up to set email alerts
|

The health effects of fetal microchimerism can be modeled in companion dogs

Abstract: Fetal microchimerism (FMC) has been described to have a range of effects on health and disease. Y-chromosomal DNA has been detected in Golden Retrievers suggesting persistent FMC. In that report, nine dogs had evidence of microchimerism without prior pregnancy. To further understand this finding, a dam with prior male live births giving birth to her fourth litter of puppies, all females, was evaluated for FMC along with two of her daughters. All three female dogs had evidence of Y-chromosomal DNA in their bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Among other families of nonhuman mammals, there are reports of natural chimerism in mice, dogs, and cats (Axiak‐Bechtel, Kumar, Hansen, & Bryan, 2013; Khosrotehrani et al, 2005; Lyons, 2012). Multiple studies have concluded that female dogs with prior male birth are able to develop persistent male microchimerism with one suggesting that these male cells could explain male chimerism in daughters of subsequent pregnancies (Axiak‐Bechtel et al, 2013; Kumar, Hansen, Axiak‐Bechtel, & Bryan, 2013). A case report of a dog with ambiguous genitalia was found to have a leukocyte XX/XY chimerism suggesting the potential for phenotypic abnormalities with canine chimerism (Szczerbal et al, 2014).…”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among other families of nonhuman mammals, there are reports of natural chimerism in mice, dogs, and cats (Axiak‐Bechtel, Kumar, Hansen, & Bryan, 2013; Khosrotehrani et al, 2005; Lyons, 2012). Multiple studies have concluded that female dogs with prior male birth are able to develop persistent male microchimerism with one suggesting that these male cells could explain male chimerism in daughters of subsequent pregnancies (Axiak‐Bechtel et al, 2013; Kumar, Hansen, Axiak‐Bechtel, & Bryan, 2013). A case report of a dog with ambiguous genitalia was found to have a leukocyte XX/XY chimerism suggesting the potential for phenotypic abnormalities with canine chimerism (Szczerbal et al, 2014).…”
Section: Animal Studiesmentioning
confidence: 99%
“…A case report of a dog with ambiguous genitalia was found to have a leukocyte XX/XY chimerism suggesting the potential for phenotypic abnormalities with canine chimerism (Szczerbal et al, 2014). Due to similarities with humans in disease and environment, dogs have been suggested to be useful models for human conditions (Kumar et al, 2013). Mice are a common model of human disease and have demonstrated pregnancy‐related chimerism similar to humans (Khosrotehrani et al, 2005; Perlman, 2016).…”
Section: Animal Studiesmentioning
confidence: 99%
“…Recently, male fetal microchimerism was identified in parous companion golden retrievers [11]. Subsequent work has also identified the phenomenon in Dachshunds, with evidence for the existence of sibling microchimerism from prior litters [12]. The suitability of these companion dogs as models is enhanced by the ease of serial sampling through local veterinary practices and breed specialty events.…”
Section: Introductionmentioning
confidence: 96%
“…In the case of the female puppies, it is unknown if each was exposed to a different dose of male cells, whether the placental interface may be more or less permissive to cell transfer, or if fetal immune reactions to haplotype differences greatly impact the quantity of identifiable microchimeric cells [12]. A large exchange of maternal and fetal cells occurs in the creation of the uterine blood vessel network that sustains the pregnancy with 12% of uterine vessel endothelium deriving from the fetus [57].…”
Section: Clinical Microchimerism Questionsmentioning
confidence: 99%
See 1 more Smart Citation